2022
DOI: 10.1038/s41598-022-14536-9
|View full text |Cite
|
Sign up to set email alerts
|

A pupillometric study of developmental and individual differences in cognitive effort in visual word recognition

Abstract: Throughout the history of modern psychology, the neural basis of cognitive performance, and particularly its efficiency, has been assumed to be an essential determinant of developmental and individual differences in a wide range of human behaviors. Here, we examine one aspect of cognitive efficiency—cognitive effort, using pupillometry to examine differences in word reading among adults (N = 34) and children (N = 34). The developmental analyses confirmed that children invested more effort in reading than adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A better characterization of these individual differences both within- and between-hemispheres, the structural and functional factors that influence them, and their association with variations in behavior across individuals warrants future research. 36 , 44 , 52 , 55 , 69 Second, the present study revealed significant engagement of the right hemisphere (particularly the STS+G) during visual word processing. Yet, the precise role played by the right hemisphere during visual word processing remains elusive, providing an exciting avenue for exploration in future research.…”
Section: Discussionsupporting
confidence: 46%
“…A better characterization of these individual differences both within- and between-hemispheres, the structural and functional factors that influence them, and their association with variations in behavior across individuals warrants future research. 36 , 44 , 52 , 55 , 69 Second, the present study revealed significant engagement of the right hemisphere (particularly the STS+G) during visual word processing. Yet, the precise role played by the right hemisphere during visual word processing remains elusive, providing an exciting avenue for exploration in future research.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, 2 articles focused on pupillary behavior during word recognition in bilinguals ( Guasch et al, 2017 ; Toivo and Scheepers, 2019 ). Finally, 2 additional articles examined pupillary dilation (cognitive effort) in different types of readers during word recognition and subsequent reading ( Shechter and Share, 2021 ; Shechter et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors project that pupillometry may offer a more sensitive moment-by-moment glimpse into the dynamics of word recognition (including developmental, interindividual, and intraindividual variation). In a second study, Shechter et al (2022) assessed the sensitivity of the pupillary response during recognition and reading aloud of a series of words in children ( N = 34) and young adults ( N = 34), who were further classified into fast/slow readers. The results showed that children showed more significant cognitive effort (as evidenced by a greater pupillary response) than adults during word recognition and reading aloud.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations